2007
DOI: 10.1017/s0025315407055853
|View full text |Cite
|
Sign up to set email alerts
|

Benthic richness in the Argentine continental shelf: the role of Zygochlamys patagonica (Mollusca: Bivalvia: Pectinidae) as settlement substrate

Abstract: In this study we present results on epibionts on Zygochlamys patagonica from material collected during monitoring cruises in different areas in the Argentine Sea. We update the checklist of epibionts increasing the number of taxa from 19 to 41 and considering two species closely associated with the shells. The demosponge Iophon proximum was the most frequent and abundant epibiont (% presence and coverage). Polydora sp. was registered as a parasite of Z. patagonica in shells from the Beagle Channel, but it did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
1
27
0
2
Order By: Relevance
“…Benthic macroinvertebrate richness at Z. patagonica fishing grounds (from by-catch samples) is estimated in more than 170 species considering motile and epibiotic species, including new species described in this area (Bremec & Lasta, 2002;Schejter & Bremec, 2007). The results of the present study increase the richness of this benthic habitat with the 24 fish species reported, although possibly many more fish species could be reported in the northern region.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…Benthic macroinvertebrate richness at Z. patagonica fishing grounds (from by-catch samples) is estimated in more than 170 species considering motile and epibiotic species, including new species described in this area (Bremec & Lasta, 2002;Schejter & Bremec, 2007). The results of the present study increase the richness of this benthic habitat with the 24 fish species reported, although possibly many more fish species could be reported in the northern region.…”
supporting
confidence: 50%
“…The commercial fleet is equipped with non-selective bottom otter trawls with booms. Since the beginning of the fishery, the identification of invertebrate by-catch and the monitoring of the benthic community associated with the Patagonian scallop fishing grounds were done (e.g., Bremec & Lasta, 2002;Schejter & Bremec, 2007;Schejter et al, 2008). The source of data for the majority of these studies were the annual research surveys, developed onboard the Instituto Nacional de Investigación y Desarrollo Pesquero (INIDEP) research vessels.…”
mentioning
confidence: 99%
“…Hiatella meridionalis (d'Orbigny, 1846) (largely misidentified as H. solida (Sowerby, 1834) (see Simone and Penchaszadeh 2008)) is a common bivalve found attached to either rocks or invertebrates, including Z. patagonica (Schejter and Bremec 2007a). In the SW Atlantic, similar records were found in Brazilian waters: H. arctica Linnaeus, 1767 was mentioned as an endobiont in Mycale (Zygomycale) angulosa (Duchassaing and Michelotti, 1864) (as Zygomycale parishii) and Mycale (Carmia) microsigmatosa Arndt, 1927, at nearly 23°S Nalesso 1996, Ribeiro et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Scallop beds in the south-west Atlantic are mainly found along the 100-m depth isobath, where there are major frontal systems (Bogazzi et al, 2005). The presence of a byssus in large individuals, and the considerable amount of epizoans (Waloszek and Waloszek, 1986;Waloszek, 1991;Sanfilippo, 1994;Schejter and Bremec, 2007) suggest that the mobility of this scallop is fairly low (Waloszek, 1991). P. patagonica lies on the substratum on its right valve (Rosso and Sanfilippo, 1991;Sanfilippo, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The role of Psychrochlamys patagonica as settlement substrate for different groups of benthic organisms has recently been analysed (López Gappa and Landoni, 2007;Schejter and Bremec, 2007). The frequency of occurrence of foraminifers, folliculinid ciliates, algae, sponges, hydrozoans, bryozoans, cirripedes, octocorals, bivalve molluscs, brachiopods, tunicates and serpulid, spirorbid and sabellarid polychaetes has already been quantified in several scallop beds along the continental shelf off Argentina (Schejter and Bremec, 2007).…”
Section: Introductionmentioning
confidence: 99%